Ricerca militare e competizione tecnologica: ambizioni, rivalità e sistemi di controllo - Palmas, Francesco (Rivista di studi politici internazionali, 2010)
This article emphasizes the utmost importance of technological research to the international balance of power. The so called ‘critical’ or ‘key’ products are the object of a gigantic, greedy competition. An economic warfare is fought about them with intent to preserve a strategic supremacy or to drain innovative hi-tech breakthroughs, regardless of how this aims are achieved. This field is considered to be the core of national power and security. The United States are the yardstick: their military strength is unrivalled and overwhelmingly financed. Not only Washington invests an average of 26.800$ per soldier, but also its defence expenses reach 48% of the world total, while the European as a whole don’t exceed 20%. In military R&D the comparison between the two powers appears even more dramatic since Brussels spends 1/6 than Washington does. Without strong support the Eu risks having to depend on the Usa in at least 20 critical technologies. What is more worrying is not the absolute amount devolved to R&D, but the scarcity of European coordination, especially in the field of ground and naval weaponry, an issue about which an Europe of Defence is still almost totally out of reach. For some, Washington is reputed to have a ten-year technological advantage over its main European allies. But in the last decade, Europe has begun to lose ground again not only with reference to the Usa, but also in the light of the emergent countries of Asia. The Americans keep support into their capabilities and their suppliers. A list of key strategic technologies is updated each year, in order to protect them rigorously and to preserve a technological gap with both enemies and allies, both banned from any participation. Cet article traite de la recherche et des transferts technologiques. Les produits dits critiques ou sensibles sont au coeur d’une gigantesque compétition. Autour d’eux se joue une guerre économique vouée d’une part au maintien d’une supériorité stratégique et d’autre part à l’acquisition, licite ou non. Dans ce secteur, qui est le nerf de la puissance et de la sureté nationale, les États-Unis priment sur les autres. Leur poids militaire n’a pas d’égal. Washington investit dans la défense le 48% du total mondial, Bruxelles moins que la moitié (20%). L’écart s’accroit en considérant les seules dépenses pour la recherche et le développement: les Européens, qui y affectent 1/6 du budget d’outre-Atlantique, se concertent peu et mal. Ils risquent de dépendre des États-Unis pour quelque vingt technologies critiques. Ils n’ont pas été à même d’aboutir à une communauté industrielle de la défense: si l’on parle d’armements terrestres et navals l’Europe n’existe pas encore. Elle perd du terrain face aux nouveaux concurrents asiatiques et n’est pas à la hauteur des enjeux même des Américains, qui protègent beaucoup mieux leur savoir-faire critique. Washington a bien des listes d’embargo et surveille depuis toujours tout ce qui peut porter atteinte à sa supériorité technologique. PAROLE CHIAVE: Ricerca militare; Tecnologie duali; Investimenti; Protezione proprietà intellettuale; Divario Usa-resto del mondo.